Governing the learned!! Corporate governance in public higher learning institutions: The Malaysian experience - Abd Ghadas, Zuhairah Ariff; Hassan, Halyani (Corporate Law Teachers Association (CLTA), 2007)
The higher education industry is in the knowledge business, both creating knowledge through research and transferring knowledge to students. The conventional view on the major role of a higher education institution is always educating students but there are many institutions, particularly the research-oriented universities which contended that the major role of higher education industry should be to generate new knowledge through research activities. Whichever view is adopted, it remains that the major assets of these institutions is knowledge, gaining reputations, students and funding based on how to deal and manage with the knowledge as the major asset. In Malaysia, the statistics published by Department of Census (DOS) in year 2000, shows that the education industry combined with the health industry are the main actors in the services sector (98.6 percent). At present there are seventeen public universities of higher learning, sixteen private universities of higher learning and hundreds of private colleges in Malaysia; educating hundreds thousands of students, of whom fifty one thousands are international students from one hundred and thirty countries. The above statistics illustrates the recognition of higher education institutions as one of the corporate actors in Malaysia. For the public higher learning institutions, the notion of doing business may not be proper as they were established to generate professional and educated human capital for the country. On the other hand, by year 2010, all Malaysian public higher learning institutions are expected to generate their own earnings to cover at least thirty percent of its expenditure and this obviously requires some entrepreneurship in the University. This paper aim to look into corporate governance structure in Malaysian public higher learning institutions and evaluate to what extent it would affect its good governance once the University divert from merely educating/ doing research to become ‘partial entrepreneurs’.